USING KHAN ACADEMY KIDS TO IMPROVE STUDENT’S READING COMPREHENSION EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL MUHAMMADIYAH PAGARALAM - pratama, yoga; Nugroho, Sigit (Jurnal Pendidikan Pemuda Nusantara, 2025)
This Study aimed to investigate the effectiveness of the Khan Academy Kids application in improving reading comprehension among eighth-grade students at Junior High School Muhammadiyah Pagaralam. The study employed a quasi-experimental design with two groups: an experimental group taught using the Khan Academy Kids application and a control group taught using conventional methods. The sample consisted of 60 students selected through purposive sampling. The data were collected through pre-tests and post-tests consisting of 40 multiple-choice questions assessing various aspects of reading comprehension such as main idea, detail, inference, vocabulary, sequence, and cloze elide. The results revealed a significant improvement in the reading comprehension scores of students in the experimental group compared to the control group. The paired sample t-test showed that the students' post-test scores in the experimental group were significantly higher than their pre-test scores, and the independent sample t-test indicated a significant difference between the experimental and control groups. These findings suggest that the Khan Academy Kids application effectively enhances students' understanding of narrative texts by engaging them in interactive and multimedia learning. Therefore, this application can be recommended as an innovative approach for teaching reading comprehension in EFL classrooms.